“Four-properties” relationship and application in the fifth member of Xujiahe Formation in Ziyang-Dongfengchang Block of central Sichuan - ZOU Yi,LIU Chengchuan,DENG Meizhou,NIU Na,HAN Zhiying (Youqicang pingjia yu kaifa)
The fifth member of Xujiahe Formation（Xu-5 member）in Ziyang-Dongfengchang Block of central Sichuan is characterized by low porosity, low permeability, and strong heterogeneity. This study aims to develop a reliable logging interpretation model and to establish the lower limits of effective reservoirs using well logging, core, and gas testing data. The research focuses on the correlation among four key properties: lithology, physical properties, electrical properties, and gas content following core homing and log normalization. A significant correlation exists between the lithology, physical properties, electrical properties, and gas content. Gamma ray readings increase as particle size decreases, aiding in sediment characterization. Resistivity curves effectively identify calcium-bearing sandstones. A strong positive correlation exists between sonic differential time and porosity. Gas content is positively correlated with physical properties, indicating richer gas zones correlate with specific log signatures. Based on these relationships, a comprehensive interpretation model for porosity, permeability, and water saturation was established, alongside criteria for reservoir identification. The application of these findings in production scenarios demonstrates consistency between reservoir logging, gas testing, and experimental results with the established four-properties relationship diagram. The calculated physical property parameters from the logging interpretation model align well with core test outcomes, and gas production profile testing corroborates the reservoir identification criteria. This study provides critical technical support for designing testing schemes and optimizing resource extraction.